Legal validity of Grace Period Renewal of Labour Agreement in Indonesia: an Example from PT. X in Sidoarjo - Muhammad Ary Taufik; Noor Fatimah Mediawati; Rifqi RIdlo Phahlevy; Mochammad Tanzil Multazam (Universitas Muhammadiyah Sidoarjo, 2019)
The employment agreement in certain time PKWT it has frequenly used by employers or companies, because it’s efficiently to carry on the company’s oparetions and can be uses to minimizing the outlay of company. In PT. X sidoarjo also uses a PKWT to their workers, but their agremeents still not appropriate with employes law. As we know that the validity of a work agreement must be contains of element and terms. So, according to the result bellow this study are used “socio legal” method. It’s means based on the facts in a field as an empirical social phenomenon. The employment agreement has valid when the signing of the employment agreement, but the agreement will be invalid when violating the rules governing. If a certain time work agreement PKWT is made unconstitutional thena certain time work agreement PKWT becomes an uncertain time work agreement PKWTT. The company will be subject to criminal sanctions if the work contract is not in accordance with the laws and regulation. This study has benefits for autors in the development of legal sciene and has benefits for the labor service, trade unions and the public who need information related to employment.